Gamma probe and ultrasound-guided fine needle aspiration cytology of the sentinel node (GULF) trial - Verver, Daniëlle (Eur J Nucl Med Mol Imaging, 2018)
PURPOSE: Sentinel lymph node biopsy (SLNB) was introduced as a minimally invasive technique for nodal staging. Since associated morbidity is not negligible, it is highly relevant to pursue a more minimally invasive alternative. The purpose of this study was to prospectively evaluate the sensitivity of fine needle aspiration cytology (FNAC) with combined gamma probe and ultrasound (US) guidance in comparison with the gold standard histology of the sentinel node (SN) after SLNB for detecting metastasis. METHODS: The study was designed as a prospective, multicentre, open-label, single-arm trial enrolling patients with newly diagnosed cutaneous melanoma or breast cancer between May 2015 and August 2017. Sample radioactivity was measured using a Mini 900 scintillation monitor. After FNAC, all patients underwent SLNB. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were estimated. RESULTS: Accrual was terminated early following an unplanned interim analysis indicating that a FNAC sensitivity of at least 80% could not be achieved. In total 58 patients of the originally planned 116 patients underwent FNAC with gamma probe and US guidance. There were no true-positive FNAC results, 14 false-negative results and one false-positive result, and thus the sensitivity, specificity, PPV and NPV of FNAC were 0%, 98%, 0% and 75%, respectively. At least 75% of the FNAC samples had a radioactivity signal higher than the background signal. CONCLUSION: FNAC with gamma probe and US guidance is not able to correctly detect metastases in the SN and is therefore not able to replace SLNB. Gamma probe-guided US is a highly accurate method for correctly identifying the SN, which offers possibilities for future research. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00259-018-4014-3) contains supplementary material, which is available to authorized users.